Oxidative Stress Attenuates TLR3 Responsiveness and Impairs Anti-viral Mechanisms in Bronchial Epithelial Cells From COPD and Asthma Patients - Menzel, Mandy; Ramu, Sangeetha; Calvén, Jenny; Olejnicka, Beata; Sverrild, Asger; Porsbjerg, Celeste; Tufvesson, Ellen; Bjermer, Leif; Akbarshahi, Hamid; Uller, Lena (Frontiers in Immunology, 2019)
COPD and asthma exacerbations are commonly triggered by rhinovirus infection. Potentially promoting exacerbations, impaired anti-viral signaling and attenuated viral clearance has been observed in diseased bronchial epithelium. Oxidative stress is a feature of inflammation in asthma and COPD and is prominent during exacerbations. It is not known whether oxidative stress affects the anti-viral signaling capacity. Bronchial epithelial cells from asthmatic and COPD donors were infected with rhinovirus or treated with the oxidative stressor H2O2 followed by exposure to the synthetic viral replication intermediate poly(I:C). Poly(I:C) was used to ascertain a constant infection-like burden. Gene and protein levels of antioxidants as well as anti-viral responses were measured 3h and 24h post poly(I:C) exposure. Rhinovirus infection and poly(I:C) stimulation induced protein levels of the antioxidants SOD1 and SOD2. In asthmatic bronchial epithelial cells pre-treatment with H2O2 dose-dependently decreased the antioxidant response to poly(I:C), suggesting exaggerated oxidative stress. Further, poly(I:C)-induced IFNb gene expression was reduced after pre-treatment with H2O2. This epithelial effect was associated with a reduced expression of the pattern recognition receptors RIG-I, MDA5 and TLR3 both on gene and protein level. Pre-treatment with H2O2 did not alter antioxidant responses in COPD bronchial epithelial cells and, more modestly than in asthma, reduced poly(I:C)-induced IFNb gene expression. Knockdown of TLR3 but not RIG-I/MDA5 abrogated impairment of poly(I:C)-induced IFNb gene expression by H2O2. We developed a method by which we could demonstrate that oxidative stress impairs anti-viral signaling in bronchial epithelial cells from asthmatic and COPD patients, most pronounced in asthma. The impairment apparently reflects reduced responsiveness of TLR3. These present findings shed light on molecular mechanisms potentially causing reduced interferon responses to rhinovirus infection at exacerbations in asthma and COPD. Together, our findings suggest a possible self-perpetuating vicious cycle underlying recurrent exacerbations, leading to an impaired anti-viral response, which in turn leads to viral-induced exacerbations, causing more airway inflammation.